Demographic Factors Mediating Organizational Commitment and Safety Performance at Ovid Construction - Eshetie Berhan; Sisay Geremew Gebeyehu; Fekadu Geremew Gebeyehu (Journal of Engineering, Project, and Production Management)
This study aimed to investigate the mediating role of demographic characteristics between organizational commitment and occupational health and safety performance at, Ovid Construction PLC, a leading private company in Ethiopia. A cross-sectional study design was employed, and a sample of 370 workers was selected using systematic random sampling. A structured questionnaire was used to collect data, and both descriptive and multivariate analysis techniques were employed. The results showed that organizational commitment positively and significantly affects occupational health and safety performance, and demographic characteristics except age positively and significantly affect occupational health and safety performance. Moreover, except aga, demographic profiles (Education Level and Work Experience) significantly and partially mediate the relationship between the two Organizational Commitment variables (Safety Measures and Work Environment) and Occupational Accident. This study highlights the importance of considering demographic factors in organizational commitment and safety training programs to improve occupational health and safety outcomes.